Obesity And Schizophrenia: A Bibliometric Analysis of Current Statements and Future Perspectives - Fithrya Dian Sari; Dira Hamimi; M. Fitrah Hidayat (International Journal Labs, 2025)
Schizophrenia is a severe mental disorder frequently accompanied by obesity as a physical comorbidity. The coexistence of these conditions worsens clinical outcomes, increases the risk of metabolic complications, and reduces treatment effectiveness. This study employed a bibliometric analysis to explore global research trends, key themes, and gaps in the literature on obesity and schizophrenia. Data were retrieved from the Scopus database in May 2025 using the keywords “obesity and schizophrenia,” yielding 4,890 relevant articles. VOSviewer software was used to visualize connections among keywords, authors, countries, and journals. Results indicated a significant rise in publications since 2005, with the United States as the leading contributor. The most frequent keywords included antipsychotic-induced weight gain, metabolic syndrome, and lifestyle intervention. The analysis revealed a strong association between schizophrenia, obesity, and the metabolic effects of antipsychotics, while research on clinical trials and negative symptoms remains limited. These findings highlight the urgent need for interventional and multidisciplinary approaches that integrate psychiatric and metabolic care. Such strategies are crucial to improving both clinical outcomes and the quality of life of patients with schizophrenia.